2014
DOI: 10.1260/1369-4332.17.12.1825
|View full text |Cite
|
Sign up to set email alerts
|

Compression Behavior of Concrete Cylinders Externally Confined by Flax Fiber Reinforced Polymer Sheets

Abstract: In this article, a bi-directional flax fiber fabric with room temperature curable epoxy was used to confine concrete cylinders. The compression performances of the confined cylinders were tested on the compressive behaviors. For comparison, unidirectional basalt fiber fabric reinforced polymer (BFRP) confined cylinders were also tested. Compared to the BFRP wet layups, the flax fiber reinforced polymer (FFRP) composite exhibits nonlinear in tension, and relatively lower tensile strength and modulus, but higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Furthermore, the dilation of confined sawdust-reinforced ice near mid-height region was more significant than that The typical failure modes of PIFFT and SIFFT specimens after the compression tests are shown in Figure 6. Both PIFFT and SIFFT specimens failed by the sudden rupture of flax FRP tubes outside the additional confinement zone at two ends accompanied by a loud popping noise, which was very similar to the failure mode of concrete-filled flax FRP tubular (CFFT) short columns under axial compression reported by Xia et al [44]. The flax FRP tubes were carefully removed after finishing the tests.…”
Section: General Observationssupporting
confidence: 71%
“…Furthermore, the dilation of confined sawdust-reinforced ice near mid-height region was more significant than that The typical failure modes of PIFFT and SIFFT specimens after the compression tests are shown in Figure 6. Both PIFFT and SIFFT specimens failed by the sudden rupture of flax FRP tubes outside the additional confinement zone at two ends accompanied by a loud popping noise, which was very similar to the failure mode of concrete-filled flax FRP tubular (CFFT) short columns under axial compression reported by Xia et al [44]. The flax FRP tubes were carefully removed after finishing the tests.…”
Section: General Observationssupporting
confidence: 71%
“…Regression analysis was commonly used to modify the expressions of BFRP-confined cylinders based on the model (Lam and Teng, 2004; Teng et al, 2009) with tested data (Campione et al, 2015; Ludovico et al, 2010; Ma et al, 2018; Xia et al, 2014). There were still controversies about the BFRP confinement effect.…”
Section: Introductionmentioning
confidence: 99%
“…Xian et al used a plain-woven flax fabric with room temperature cured epoxy to confine concrete cylinders (Fig. 23) [50]. The compressive results showed that flax fabric-reinforced composite improved ultimate strain and stress of the cylinders by more than ten-and twofold, respectively, depending on the fabric layers applied.…”
Section: Development Of Quasi-structural and Function-integrated Compmentioning
confidence: 99%